The Rising Prevalence of Chronic Low Back Pain() - Freburger, Janet K. (Arch Intern Med, 2009)
BACKGROUND: National or state-level estimates on trends in the prevalence of chronic low back pain (LBP) are lacking. The objective of this study was to determine whether the prevalence of chronic LBP, and the demographic, health-related, and care-seeking characteristics of individuals with the condition have changed over the past 14 years. METHODS: A cross-sectional, telephone survey of a representative sample of North Carolina (NC) households was conducted in 1992 and repeated in 2006. 4,437 households were contacted in 1992 and 5,357 households were contacted in 2006 to identify noninstitutionalized, adults 21 years and older with chronic, impairing (pain>3 months that limits daily activities). These individuals were interviewed in more detail about their health and care-seeking. RESULTS: The prevalence of chronic, impairing LBP rose significantly over the 14 year interval, from 3.9% (95% CI:3.4–4.4) in 1992 to 10.2% (95% CI:9.3–11.0) in 2006. Increases were seen for all adult age strata, in males and females, and in white and black races. Symptom severity and general health were similar for both years. The proportion of individuals who sought care from a health care provider in the past year increased from 73.1% (95% CI:65.2–79.8) to 84.0% (95% CI:80.8–86.8), while mean number of visits to all providers were similar (19.5 vs 19.4). CONCLUSIONS: The prevalence of chronic, impairing LBP has risen significantly in NC, with continuing high levels of disability and care utilization. A substantial portion of the rise in LBP care costs over the past two decades may be related to this rising prevalence..